Exploring the world of active play: A comprehensive review of global surveillance and monitoring of active play based on the global matrix data - Eun-Young Lee; An-Chi Shih; Mark S. Tremblay (Elsevier, 2024)
A valid assessment tool that measures active play is not yet available due to the sporadic and spontaneous nature of play, as well as the potential differences in how active play is understood and measured across different age groups, cultures, and contexts. The purpose of this review was to identify the scope and gaps in the measurement of active play based on data gathered from 68 countries that participated in the Global Matrix (GM) initiative, led by the Active Healthy Kids Global Alliance (AHKGA). GM is the global-level, biennial evaluation system of physical activity related behaviors among children and youth, including the Active Play indicator, and the sources of influence using letter grades (ranging between "A" and "F"). Based on the identified scope and gaps, this study offers recommendations for future research dedicated to the measurement/surveillance of active play. Out of the 68 countries involved in the previous GM (2014-22), 55% of the grades remained unassigned due to insufficient data on the Active Play indicator. The high number of unassigned grades, combined with the absence of valid measurement tool, highlight a need for a standardized measurement tool for improved global data generation of active play among children and youth. Our findings emphasize the need to address challenges in measuring active play. This review offers future considerations, research recommendations specific to the GM initiative, and two sets of age- and location-specific (indoor and outdoor settings) questionnaire items along with guidelines for its use. Together, these elements provide a roadmap for guiding future research and evaluation efforts on active play.